Konteks Tuturan dalam Cerita Anak Durhaka Ojuang yang terdapat di Kabupaten Kuantan Singingi Riau - Musliha Wardana; Khalidatun Nuzula; Mita Domi Fella Henanggil; Sri Antoni (BHASWARA: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study is motivated by the importance of examining folklore as intangible cultural heritage, particularly the legend of "Anak Durhaka Ojuang" from Kuantan Singingi Regency, which is rich in moral values but rarely analyzed from a pragmatic linguistics perspective. This research aims to identify and analyze the speech context, types of speech acts, and cultural values embedded in the story. A descriptive qualitative method with discourse analysis was employed, utilizing Austin and Searle's speech act theory and Kluckhohn's cultural value framework. Data were collected through in-depth interviews with a native storyteller and textual analysis of the narrative. The results reveal an informal narration context, yet key utterances—such as Ojuang's denial and his mother's curse—function as declarative speech acts that reproduce the community's cosmological values. The story serves as a mechanism for social control and character education, emphasizing filial piety, religiosity, solidarity, and work ethic. It is concluded that the Ojuang legend is an effective value maintenance system where language acts not merely as a communication tool but also as an instrument for enforcing cultural norms. These findings contribute to folklore research methodology with an integrated linguistic approach.